Pengelompokan UMKM Kota Binjai Menggunakan Metode Clustering K-Means Untuk Mengidentifikasi Pola Perkembangan Bisnis - Intan Sari; Yani Maulita; Lina Arliana Nur Kadim (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
Grouping is a process or activity to develop a system that is more organized and easy to understand, making it easier to analyze, identify or manage data and can also be used to explore information so that it becomes new knowledge for anyone who wants to obtain it. and in this case the information we want to explore is about MSME data in Binjai City. Namely, it is difficult to know how to identify existing business development patterns, whether they are not yet developed, less developed, already developed, and very developed. Offline and online promotions have not been optimal in increasing the growth and change of a business from time to time. And most MSMEs still don't understand how to market their products and services effectively and efficiently. MSMEs are one of the most numerous community business groups in Binjai City. To obtain this information, one solution that can be implemented is by utilizing data mining using input data in the form of Binjai City MSME data. This data will be processed using the clustering method with the k-means algorithm using MSME business type variables, sales type variables and development pattern variables. .Based on the results of grouping Binjai City MSMEs using the K-Means Clustering Method from 20 grouped data, 3 clusters and 2 iterations were obtained where cluster 1 contained 4 data and was located in the MSME business type group, namely the businesses included in this cluster were businesses in the field of Fashion, for the sales type group, uses online and offline types, and for business development patterns, it has a development pattern that has developed. cluster 2 has 11 and is located in the MSME business type group, namely the businesses included in this cluster are businesses in the culinary sector, for the sales type group the offline type is used, and for the business development pattern it has a development pattern that has developed. and cluster 3 has 5 data and is located in the MSME business type group, namely the businesses included in this cluster are businesses in the culinary sector, for the sales type group it is using the offline type, and for the business development pattern it has a less developed development pattern. so it can be concluded that the pattern of business development of Binjai City MSMEs produces relevant data so as to produce designs that can be used for this research.